Analysis of Electronic Medical Records (EMR) Implementation at Pratama Hidayah Clinic Using the SWOT Method: Analisis Implementasi Rekam Medis Elektronik (RME) di Klinik Pratama Hidayah dengan Metode SWOT - Engkesa, Penina Apricia; Guswin, Instreet; Meisiana, Rista; Fitriyaningsih, Dwi; Saputri, Yunitya; Widiyanto, Wahyu (Jurnal Rekam Medis dan Informasi Kesehatan, 2025)
The implementation of Electronic Medical Records (EMR) is a crucial part of the digital transformation of healthcare services in Indonesia, including at the Pratama Hidayah Clinic. This clinic has implemented an EMR system integrated with SATUSEHAT since early 2024 in response to Minister of Health Regulation No. 24 of 2022. This study aims to evaluate the implementation of EMR at the Pratama Hidayah Clinic using a descriptive qualitative approach through observations and interviews with medical records and IT staff. The results indicate that although the system has been operating quite well and no data breaches have been reported, several significant obstacles remain, such as the lack of integration with BPJS Kesehatan (Social Security Agency for Health), limited operational time, a lack of security and authentication systems, and the absence of an adequate data backup system. Furthermore, the referral process is still manual, and physical documentation is poorly organized. However, there is potential for development through BPJS integration, the implementation of online referrals, and increased operating hours with additional human resources. Improvements are needed, particularly in aspects of system security, data management, and service integration, to enhance the quality and efficiency of healthcare services at the Pratama Hidayah Clinic.